Comprehensive review on the role of salinity on oil recovery mechanisms during chemical flooding - Nyah, Francis; Norida, Ridzuan; Nwaichi, Peter Ikechukwu; Umunnawuike, Chika; Agi, Augustine Aja (Elsevier, 2024)
Previous studies have reported contradictory behavior on the influence of salinity on enhanced oil recovery (EOR) chemicals like surfactants, polymers, and nanoparticles among others. This uneven agreement of data and huge variation of experimental results indicates that the effect of salinity on EOR mechanisms is still tenuous in literature. This research presents the recent advances in the influence of salinity on EOR mechanisms and the applications of salinity in EOR. Therefore, the main objective of this research is to draw an informed conclusion on the debate regarding the impact of salinity on oil recovery so that geologists, reservoir, petroleum, and chemical engineers from academia and industry may have a clear standpoint on the impact of salinity on EOR mechanisms. Herein, reservoir salinity was discussed. The effect of salinity on EOR mechanisms was reviewed. Likewise, the application of salinity to oil recovery was elucidated. Finally, the challenges encountered during nanofluid, surfactant, alkaline, foam, and polymer flooding have brought light novel concepts for research which are highlighted herewith proffered technical solutions. Experimental results indicate that the optimal salinity thresholds for augmenting recovery typically fall within the range of 1000 to 6000 ppm. Therefore, it is recommended to maintain salinity below 5000 ppm in laboratory scale experiments and 3000 to 10,000 ppm in field conditions. Most literature has proposed fines migration as an EOR mechanism during low salinity water flooding (LSWF). However, there is no correlation between clay fines migration and EOR, indicating that EOR during LSWF is not caused by fines migration but rather by the injected fluid.